ANALISIS PENGGUNAAN METODE MIND MAPPING DALAM PEMBELAJARAN IPAS MATERI CAHAYA DAN SIFATNYA DI SDN DURI KEPA 17 PAGI - Pandini, Intan; Halim, Abdul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to analyze the use of the mind mapping method in science and science learning about light and its properties at SDN Duri Kepa 17 Pagi. The method used in this research is a descriptive qualitative method with data collection techniques in the form of observation, interviews and documentation. The result ofthis research is that the use of the mind mapping method can help students think more critically when creating the mind map. Because mind mapping teaches students to understand a concept or meaning of a lesson and gives students the freedom to form a mind map. Mind mapping also helps students understand the relationship between various concepts related to light. For example, students can see how the concept of reflection relates to refraction through branches that showinteractions between light and different media. It can be concluded that by using this mind mapping method, a creative, interesting learning atmosphere can be created,and students are able to present in front of their friends because the language used is short and in accordance with what they summarize. The use of the mind mappingmethod in science learning, especially regarding light and its properties, has proven to be effective in increasing students' understanding. Mind mapping helps students to organize information in a structured and visual way, making it easier for them toidentify and remember key concepts such as light sources, properties of light, and their practical applications.